Selection Of Gas Condensate Wells To Increase Condensate Recovery In Gas Condensate Fields - Abdirazakov Akmal Ibrahimovich; Bekmurodov Bakhtiyor Bokhodir o‘g‘li; Abduraxmonov Xusniddin Abduraxmon o‘g‘li (Genius Journals, 2024)
This article describes the conditions for selecting wells and the sequence of processes performed when influencing wells to increase condensate recovery in gas condensate fields
Keywords: well; processing; magnetite; plastic